Digitalization of Waqf Accounting: A Systematic Review of the Role of Technology in Waqf Governance - Wali Saputra (Teewan Journal Solutions, 2025)
The objective of this research is to systematically evaluate the influence of technological advancements on the digitization of waqf accounting and its subsequent effects on enhancing transparency, accountability, and efficiency within waqf governance frameworks. Employing the Systematic Literature Review (SLR) methodology alongside the PRISMA guidelines, a total of 31 pertinent scholarly articles were meticulously selected from a range of international databases, including Scopus, ScienceDirect, and Google Scholar. The findings indicate that the integration of information technology, particularly through digital-based accounting information systems, has significantly augmented reporting efficiency and bolstered public trust in waqf management practices. Furthermore, technological innovations such as blockchain, sharia fintech platforms, and the tokenization of waqf assets are progressively being implemented, albeit they continue to encounter challenges concerning regulatory frameworks, human resource preparedness, and digital infrastructure. The review advocates for the formulation of national standards for digital waqf accounting systems, the enhancement of regulatory frameworks and digital literacy initiatives, as well as the establishment of strategic partnerships between waqf institutions and technology providers. This research offers substantial contributions to the comprehension of the transformation occurring within waqf governance in the context of the digital era and paves the way for further scholarly inquiry into the development of a sustainable, values-driven digital waqf model grounded in Islamic principles.